DAMPAK PEMBANGUNAN INDUSTRI PARIWISATA TERHADAP ALIH FUNGSI LAHAN - Miswanto Miswanto; Mat Safaat (Universitas Andalas, 2018)
Riau Islands as one of the tourism destinations in Indonesia that has unique tourist uniqueness. The uniqueness and potential of tourism in the Riau Islands is developed as one of the tourism destinations based on culture and supported by the beauty of nature is very interesting. The emergence of maritime tourism as the most popular place impacts the tourism in the Riau Islands region. Many changes occur due to the development of tourism. However, the most attention is the high level of tourism accommodation development with a very limited amount of land. The limitation does not necessarily stop development and even leads to a higher level of functional alteration that threatens the existence of green open spaces that also impact to other areas as happened in Teluk Village Mangrove, Gunung Kijang District. Beside that, the lack of human resources, especially in Teluk Bakau Village, Gunung Kijang Sub-district, is still not able to compete in tourism sector either in local, national or international scale. If this is left is not impossible that tourism was originally expected to be able to improve the welfare of society it will threaten the welfare of the community itself. Intangible is seen there is a movement of people who are now tend to orient towards profit financially or profit oriented. Because, tourism industry is seen as a profitable activity and able to bring in great revenue.namun, reality in the field shows that the development of Tourism Village has not been side with the community of Teluk Bakau Village. As the development of coastal tourism is a tourism asset sold for tourist satisfaction. However, the development of tourist villages is not aligned with people's lives. The socio-economic life of the Bakau Bay community is unchanged while investors reap huge profits from this tourism activity. In fact, if there is no coastal tourism industry tourism in Teluk Bakau Village will not grow